The Influence of Social Support and Self-esteem on Subjective well-being of High School Student in Bandung City - Ifa Hanifah Misbach; Sri Maslihah; Ira Mutiara Rusli (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2023)
This study aims to determine the effect of social support and self-esteem on subjective well-being of high school students in Bandung city. The author used a quantitative method with 455 respondents of high school student in Bandung. The instruments are Student Social Support Scale by Nolten (1994) modified by Malecki and Elliott (1999) to measure the social support of parents and peers, The Three Esteem Dimensions compiled by Stets and Burke (2014) modified by Adiba (2020) to measure self-esteem, the Scale of Positive and Negative Experience (SPANE) and Satisfaction with Life Scale (SWLS) which have been modified by Adzhani (2019) to measure subjective well-being. The data analysis technique is linear regression and multiple regression. This research found that: 1) There is a significant effect of social support and self-esteem on subjective well-being; 2) There is a significant effect of parental social support on subjective well-being; 3) There is a significant effect of peer social support on subjective well-being; 4) There is a significant effect of self-esteem on subjective well-being.